Risk of Severe Influenza Among Adults With Chronic Medical Conditions. (4th November 2019) - Walker, Tiffany A; Waite, Ben; Thompson, Mark G; McArthur, Colin; Wong, Conroy; Baker, Michael G; Wood, Tim; Haubrock, Jennifer; Roberts, Sally; Gross, Diane K; Huang, Q Sue; Newbern, E Claire
Abstract: Background: Severe influenza illness is presumed more common in adults with chronic medical conditions (CMCs), but evidence is sparse and often combined into broad CMC categories. Methods: Residents (aged 18–80 years) of Central and South Auckland hospitalized for World Health Organization-defined severe acute respiratory illness (SARI) (2012–2015) underwent influenza virus polymerase chain reaction testing. The CMC statuses for Auckland residents were modeled using hospitalization International Classification of Diseases, Tenth Revision codes, pharmaceutical claims, and laboratory results. Population-level influenza rates in adults with congestive heart failure (CHF), coronary artery disease (CAD), cerebrovascular accidents (CVA), chronic obstructive pulmonary disease (COPD), asthma, diabetes mellitus (DM), and end-stage renal disease (ESRD) were calculated by Poisson regression stratified by age and adjusted for ethnicity. Results: Among 891 276 adults, 2435 influenza-associated SARI hospitalizations occurred. Rates were significantly higher in those with CMCs compared with those without the respective CMC, except for older adults with DM or those aged <65 years with CVA. The largest effects occurred with CHF (incidence rate ratio [IRR] range, 4.84–13.4 across age strata), ESRD (IRR range, 3.30–9.02), CAD (IRR range, 2.77–10.7), and COPD (IRR range, 5.89–8.78) and tapered with age. Conclusions: Our findings support the increased risk of severe, laboratory-confirmed influenza disease among adults with specific CMCs compared with those without these conditions. Abstract : Population-based surveillance of acute respiratory infections among Auckland, New Zealand residents during 2012–2015 revealed significantly higher incidence and risk of influenza-related hospitalizations in adults with chronic medical conditions, with the largest effects occurring in CHF, ESRD, CAD, and COPD.